rare cause of recurrent hemoptysis - Meta Jevtović, Ivana; Suša, Romana; Đokić, Bojan (Medicinski časopis, 2021)
Pulmonary arteriovenous malformation is a rare disorder of pulmonary vascularization. We are going to describe the case of recurring hemoptysis with the patient who was diagnosed late with pulmonary AV malformation. The 68-year-old patient was hospitalized for the fourth time in the Clinic for Pulmonology, Clinical Center of Kragujevac due to recurring hemoptysis. Bronchoscopy was conducted which showed no signs of bleeding nor new changes in the bronchial lumen. MSCT of the chest eliminated the possibility of bronchiectasis as the cause for hemoptysis. Chest MSCT was repeated, and was without evolutionary aspect when compared to a previous. In April 2019, at the Military Medical Academy in Belgrade, the patient had bronchoscopy performed, the results were normal, and the examination was completed with exploration, along with selective angiography, where AV shunt could be seen on the left side. Since the diameter of the left bronchial artery was less than 2 mm, it was not possible to place the micro-catheter and do embolization, but hemostasis was done by manual compression, which lasted for 10 minutes. After six months of follow-up examinations, no complications were registered with the patient. The method of choice for diagnosing PAV malformation is bronchial angiography, while other chest radiographic methods are not reliable. Embolization is the method of choice for treating this disorder.